Electrochemically fabricated nanovolcano arrays for SERS applications. (2nd October 2012) - Tsang, Chun Kwan; Shu, Shiwei; Liang, Fengxia; Zhang, Jie; Zheng, Lingxia; Li, Yang Yang
<x xml:space="preserve">Abstract</x> Nanovolcano arrays were fabricated by electrodepositing Ni/Cu alloys into a monolayer of self‐assembled nanospheres and then electrochemically etching the deposited alloy film. The fabricated nanovolcano arrays feature highly ordered hexagonally arranged concave nanobowls decorated with triangular nanopores at their interstices. After coated with Ag, the nanovolcano arrays serve as high‐performance substrates for surface enhancement Raman spectroscopy (SERS) measurements. The experimental study shows that the structural features of the nanovolcano arrays, including concave nanobowls, nanopores, and their long‐range orders, all contribute to the observed strong SERS enhancement in a synergetic manner, which is further confirmed by the simulation results obtained using the finite‐difference time‐domain method. Copyright © 2012 John Wiley & Sons, Ltd.